Lumbosacral discopathy: analysis of physical therapy - Fronczyk, Katarzyna; Kuliński, Włodzisław (Medical Studies/Studia Medyczne, 2017)
Introduction : Spinal pain syndromes are one of the most common medical conditions of the 21st century. Spinal pain syndromes are usually associated with degenerative disease and discopathy. Their incidence has been growing alarmingly year by year in all countries of the world. Studies show that sacral pain occurs in as many as 80% of adults and 39.5% of teenagers. Aim of the research: To analyse physical therapy and rehabilitation of patients suffering from lumbosacral discopathy. Material and methods : The study encompassed a group of 54 patients with lumbar disc disease. The subjects were aged 20–60 years. The research tool consisted of a questionnaire prepared by the authors. This survey included 17 closed questions and five open ones. The results were assessed with two subjective scales of pain intensity: a VAS scale and the Laitinen pain indicator. Moreover, Schober’s test was also used to assess lumbosacral mobility. Results : The research shows that the rehabilitation introduced in the patients contributed to a reduction in pain. The treatment resulted in pain relief, a lower frequency of pain episodes, a lower frequency of taking analgesics, and less physical activity limitations. The rehabilitation also had a significant impact on the improvement of lumbosacral spine mobility. Conclusions : Physical therapy and rehabilitation constitute the basis for the treatment of patients with spinal pain syndromes.